Impact of thrombolytic therapy on basilar artery occlusion patients with atrial fibrillation: results from a multi-center prospective cohort study - Shang, Xianjin; Chu, Longsheng; Chen, Heming; Yang, Ke; Yang, Qian; Hu, Wei; Xu, Jie; Zhou, Zhiming (Frontiers in Neurology, 2025)
BackgroundThe benefits and risks of intravenous thrombolysis combined with endovascular treatment for basilar artery occlusion patients with atrial fibrillation (AF) are uncertain. This research investigates the disparities in the impact of bridging thrombolysis on the long-term prognoses of endovascular treatment between patients with AF and those without it.MethodsWe analyzed data from a Chinese multi-center prospective registry conducted between March 2017 and February 2023. Primary analysis included favorable (mRS 0–2) and good (mRS 0–3) outcomes at 3 months, the risk ratio (aOR) and 95% confidence interval for the outcome associated with bridging thrombolysis were calculated using multivariate regression analysis. Subgroup analyses evaluated the relative excess risk index (REPI) for AF and intravenous thrombolysis.ResultsAmong 1,368 patients, the ratio of AF to non-AF patients was 434:934, the proportion receiving intravenous thrombolysis was 101 vs. 226. In the AF group, thrombolysis improved functional prognosis (aOR 1.93, 95% CI 1.14 to 3.29, p = 0.01 for favorable; aOR 2.06, 95% CI 1.23 to 3.46, p = 0.006 for good outcomes), with no differences in the non-AF group. Cross-stratification analysis indicated that AF patients receiving thrombolysis had the highest rates of favorable (aOR 1.99, 95% CI 1.27 to 3.11, p = 0.002) and good outcomes (aOR 2.11, 95% CI 1.35 to 3.30, p = 0.001), suggesting a significant additive effect of the treatments (REPI 0.89, 95% CI: 0.07–1.71; p = 0.02 and REPI 1.13, 95% CI: 0.24–2.02; p = 0.004).ConclusionThe presence of AF modified the treatment effect of bridging thrombolysis in basilar artery occlusion. These findings warrant confirmation through RCT studies.